THE INFLUENCE OF HUMAN RESOURCE COMPETENCY ON EMPLOYEES PERFORMANCE - Indah Kusumah Hayati (The Management Journal of Binaniaga, 2017)
Competition requires every organization to increase the quality in their competitiveness by using high quality and competent human resources. The competency should be beyond academic and working skills alone, and should include attitude as well. Inefficient quality and competency of human resources results in declination of work effectiveness. The goal of this research is to elicit whether there is positive impact on the increase of competency toward working effectiveness. The object of this research is employees at the Secretariate Directorate General of Human Resources and Post and Informatic Devices (Secretariat General SDPPI). Variable indicator of the competence studies includes knowledge, ability and attitude. Data analysis to test the hypothesis is done using multiple linear regression, determination coefficient, F-test and T-test analysis. From the three independent variables that were individually tested, the most dominant compensation that affects work effectiveness of workers is knowledge, with a coefficient of 0.366. F-test analysis showed that knowledge, ability and attitude, all together has positive effect toward workers’ work effectiveness.Keyword: competency, work effectiveness